Research and Application of IT Indicator Management Oriented User Experience - Wenfeng Lin; Guowen Huang (Dianxin kexue)
To evaluate the user experience of IT systems, building up a user experience oriented IT key performance indicator architecture, which is the foundation of transferring the IT management from the infrastructure monitoring and analysis to service monitoring and analysis. Based on the lot of real world's new requirements of the IT service management, the architecture of user experience oriented IT key performance indicator was analyzed and designed, and an application management effectiveness platform or system was implemented, via the platform, could automatically and effectively monitor and analyze the IT systems.